The Relationship of Culture with the Formation of Kurdish Individual Personality: It is a theoretical study (Raparin Journal of Humanities (RJH), 2024)
This research is entitled (The Relationship of Culture with the Formation of Kurdish Individual Personality). It is theoretical research. For the purpose of knowing the relationship of cultural aspects such as tradition and social value on the formation of the Kurdish individual personality. culture has a major role on forming the Kurdish individual personality. They can generate an individual that they want, since value, direction, norm, and tradition are the measures that help individuals in the form of general culture of society so as to adjust with the environment that live in it.The problem of the study is that the Kurdish individuals have been lived in instable society along the history, because of that they could not carry out their special intentions. Besides, they were not able to make a decisive decision concerning the variations’ process of cultural aspects.The significance of the research is to indicate the role of culture on the behaviour of Kurdish individual’s reaction and tied relationship. Meanwhile, the most significant aim of the study was indicating the role of tradition and social values on the behaviour of Kurdish individuals.The most significant result of the study was the complication of Kurdish society’s social system.  The Kurdish individuals have always distanced itself from breaking its cultural aspects, as if it breaks the rules and laws of society, it will face difficulty. If it repeats again, It will be looked as a lawbreaker, so it will make an impact on social values inside community and family as well.The most important recommendation for the future researchers is that they should do more studies on traditions and social values related to the formation of the Kurdish individual personality. Moreover, they should pay more attention to more scientific studies Kurdish individuals’ social values.